Effects of supplementing hemp (Cannabis sativa L.) leaves in concentrate diet on carcass traits and meat characteristics of Longissimus muscle in goat kids - Chanporn Chaosap; Katatikarn Sahatsanon; Kazeem D. Adeyemi; Korawan Sringarm; Jamlong Mitchaothai; Achara Lukkananukool (PLoS ONE, 2025)
The influence of dietary hemp ( Cannabis sativa L.) leaf (HL) supplementation in a concentrate diet on carcass traits, physicochemical properties, amino acids, ribonucleotides, lipid oxidation, and fatty acids of Longissimus thoracis et lumborum (LTL) muscle in goat kids was evaluated. Fifteen entire Thai native x Boer bucks (body weight: 16.28 ± 0.35 kg; age: 4 months) were randomly assigned to concentrate diets containing 0% (HL-0), 2% (HL-2), or 4% (HL-4) HL for 150 days, after which they were slaughtered. The LTL muscles were assessed for physicochemical properties, fatty acids, amino acids, ribonucleotides and lipid oxidation. The HL-4 goats had heavier hot and cold carcass weights compared to the other groups ( P < 0.05). Shoulder percentage was lower in the HL-0 goats than in the other groups ( P < 0.05). The diets did not affect color, chemical composition, shear force, muscle fiber diameter, sarcomere length, ribonucleotides, or free and total amino acids in the LTL muscle in goats. However, the HL-4 meat had higher ( P < 0.05) pH 24 h compared to the HL-2 meat, while the pH of the HL-0 meat did not differ from that of the other groups. The HL-4 meat had lower cook loss compared to the other meats ( P < 0.05). HL supplementation increased C20:4n-6 concentration ( P < 0.05). HL-2 meat had higher total polyunsaturated fatty acids compared to the other groups (P < 0.05). The HL-2 and HL-4 meats had lower TBARS values ( P < 0.05) throughout the 5-day postmortem chill storage. Dietary inclusion of 2–4% hemp leaves improved carcass yield, fatty acids, and oxidative stability of goat meat without compromising other quality traits, suggesting its potential as a natural feed additive to enhance meat quality and shelf life.